Coach competences to induce positive affective reactions in sport and exercise - A qualitative study - Strauch, U. G.; Wäsche, H.; Jekauc, D. (Sports, 2019)
Positive affective reactions are a crucial aspect in physical activity maintenance. Affective reactions to sport and exercise were found to be important factors of physical activity. Coaches could be an important medium to induce positive affective reactions of participants in sport and exercise. Understanding how coaches trigger positive affective reactions (AR) during physical activity is a crucial aspect for increasing maintenance in sport and exercise. The aim of this study is to identify the competences of the coaches which are associated with perceived positive AR of participants during sport and exercise. To identify these factors, semistructured in-depth interviews were conducted with 18 participants, who take part in sport and exercise (nine female and nine male) of heterogeneous age (mean age 42.6; SD = 19.25; under 30 years, 30 to 60 years, 60 years and above) and who have different athletic backgrounds (individual sports, team sports, and gym classes). Four key coach competence factors were identified and used to design an integrated model. Three general competences: context sensitivity, social-emotional competences, professional competences, and the specific competences in the behaviour-related competences.